2021
DOI: 10.1007/s00213-021-05823-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cannabidiol (CBD) expectancy effects on acute stress and anxiety in healthy adults: a randomized crossover study

Abstract: Rationale Cannabidiol (CBD) has been reported to attenuate stress and anxiety, but little is known about the extent to which such effects result from pharmacological versus expectancy factors. Objectives We evaluated whether CBD expectancy alone could influence stress, anxiety, and mood, and the extent to which beliefs regarding CBD effects predicted these responses. Methods In this randomized crossover study, 43 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…In previous clinical research, melatonin has been shown to have modest effects on sleep relative to placebo, 48 though clinical evidence of CBD's effect relative to placebo remains limited, albeit promising. [23][24][25] Notably, previous clinical research suggests that placebo response could play a major role in the effect of CBD on stress and anxiety, 49 though the impact of this response has yet to be explored for CBD and sleep. Further placebo-controlled studies are needed to determine the therapeutic effects of CBD for sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical research, melatonin has been shown to have modest effects on sleep relative to placebo, 48 though clinical evidence of CBD's effect relative to placebo remains limited, albeit promising. [23][24][25] Notably, previous clinical research suggests that placebo response could play a major role in the effect of CBD on stress and anxiety, 49 though the impact of this response has yet to be explored for CBD and sleep. Further placebo-controlled studies are needed to determine the therapeutic effects of CBD for sleep.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed more frequently in male patients. Human laboratory experiments suggest that patient's expectations play a major role in both the analgesic and anxiolytic effects of CBD ( 34 , 35 ). Therefore, overemphasizing the analgesic potential of CBD could result into negative treatment outcomes when such expectations are not met ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CBD-OEQ may also be useful for clinical trial or administration research, as emerging research suggests that preexisting CBD-related outcome expectancies influence subjective effects (e.g., anxiety reduction) of CBD regardless of actual pharmacology (Spinella et al, 2021). The CBD-OEQ could be used to expand upon the Spinella et al (2021) administration study by testing whether CBD-OEQ subscales moderate the relationship between administration condition and other outcomes of interest. For example, researchers could test whether the CBD-related pain expectancy subscale (collected prior to administration of CBD) moderates the relationship between condition and subjective reports of pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study is somewhat limited by using single items to assess expectancies and not assessing desirability ratings of the expectancies, which is problematic because isolating expectancy from value ratings and their interaction is important for understanding outcome expectancies. It may also be important to assess and understand other expectancies (e.g., sleep, pain) that are beyond the scope of the Spinella et al (2021) study. Yet, no known CBD-specific outcome expectancy measure exists.…”
mentioning
confidence: 99%
See 1 more Smart Citation